Geographic Names Information System (GNIS) - Geological Survey (U.S.); United States Board on Geographic Names (Reston, VA : U.S. Dept. of the Interior, U.S. Geological Survey, 1995)
Database for feature names authorized by the U.S. Board on Geographic Names. GNIS data includes information on place names, features, and areas in the 50 states, the District of Columbia, territories and outlying areas of the United States, and Antarctica. Web site also provides links to other geographic information servers.
Title from web page last updated Mar. 27, 2008 (viewed Mar. 27, 2008).
Searchable database
Mode of access: Internet via the USGS web site. Address as of 4/11/01: http://geonames.usgs.gov ; current access is available via PURL.
Also issued on CD-ROM, ending with issue for 1999.
Keywords: Names, Geographical -- United States -- Databases; Names, Geographical -- Antarctica -- Databases; United States -- Gazetteers -- Databases; Antarctica -- Gazetteers -- Databases; United States -- Maps -- Databases; Topographic maps